2015
DOI: 10.3141/2480-06
|View full text |Cite
|
Sign up to set email alerts
|

Transportation Engineering Instructional Practices

Abstract: Instructional practices in transportation engineering education are evolving, and only some of these changes have been documented in the literature. This paper provides a systematic review of journal articles and refereed conference papers that address innovations in transportation engineering education; the focus is on novel instructional practices and their influence on student learning. The literature review finds 46 articles for analysis, with an increasing frequency of those publications over time. Instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Besides the development of curricula as a critical aspect for the development of competencies of future TE professionals [12], there have been a series of efforts in developing educational practices. A recent comprehensive review of advances of TE teaching practices classifies them into simulation, visualization, experience-and problem-based learning, and other active learning techniques [14]. Moreover, this review concluded that there is a need to further improve the assessment practices for evaluating changes in teaching practices and student learning [14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the development of curricula as a critical aspect for the development of competencies of future TE professionals [12], there have been a series of efforts in developing educational practices. A recent comprehensive review of advances of TE teaching practices classifies them into simulation, visualization, experience-and problem-based learning, and other active learning techniques [14]. Moreover, this review concluded that there is a need to further improve the assessment practices for evaluating changes in teaching practices and student learning [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hurwitz et al 3 describes in detail the literature reviewed in response to the research questions related to instructional practices and measurement of student learning. Forty-six papers met the inclusion criteria for these research questions.…”
Section: Results From the Systematic Literature Review In Transportatmentioning
confidence: 99%
“…The following sections summarize the methodology provided in Borrego et al and use the recently completed systematic literature review in transportation engineering as a case study to show how the methodology can be applied 1,3 .…”
Section: Performing a Systematic Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations